Psychological Education in Overcoming Trauma Due to Natural Disasters - Frisca Reggina; Eva Indriani (Tinta Emas Institute, 2023)
This research aims to explore the role of educational psychology in overcoming trauma resulting from natural disasters, with a focus on case studies of flood disasters. Natural disasters, such as floods, often cause significant psychological impacts on individuals, especially children and adolescents. In this context, educational psychology has an important role in providing psychological support, facilitating recovery, and building psychological resilience in disaster victims. This research uses a qualitative approach with a specific flood case study to evaluate educational psychology strategies that have been used to overcome trauma caused by natural disasters. The findings of this study highlight the importance of person-centred and evidence-based approaches in helping individuals cope with the psychological impacts of natural disasters, as well as offering insight into how education can be an effective tool in building psychological resilience and supporting post-disaster recovery. This study has the potential to provide practical guidance for professionals in the fields of educational psychology, education, and disaster relief to provide better support to those affected by natural disasters, especially floods.